If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-3=2(2x+3)-3
We move all terms to the left:
5x-3-(2(2x+3)-3)=0
We calculate terms in parentheses: -(2(2x+3)-3), so:We get rid of parentheses
2(2x+3)-3
We multiply parentheses
4x+6-3
We add all the numbers together, and all the variables
4x+3
Back to the equation:
-(4x+3)
5x-4x-3-3=0
We add all the numbers together, and all the variables
x-6=0
We move all terms containing x to the left, all other terms to the right
x=6
| x+1÷4-2=3 | | 2(-41/2+3=4(m-3)+51/2 | | -3m(2m-7)=0 | | x+1/4-2=3 | | -43=-y|3 | | Y+y/2=900 | | x-7+x=85 | | x^2+x9-36=0 | | a-2.01=5.5 | | s+49=3s+11 | | 1/4(4t-7)=t+7/8 | | t+44=2t+26 | | 5/x+4-7/x-4=12/x^2-16 | | -3(x+6)=-36 | | 4(b-2)=-4b-8(5+b) | | 10c=13.71 | | Y2+7y=-10 | | P(x)=-0.5x^2+40x+300 | | 5x-13=2x-9-3+3x | | 0=1/5x+3 | | 36+9/8r=-36 | | 4/3y-8=-4 | | 100d=13.71 | | 7t=t+48 | | 3x+(15x+18)=180 | | 2.25t=13.5t+9 | | 1/(2x)=-56 | | 4x2-11x=x-9 | | -2(8v-2)=100 | | -11.2+4(2.1+a)=0.8 | | 20x-(6x-7)=63 | | 9-(2y-4)=2-3y |